2020
DOI: 10.1038/s41598-020-73296-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of brain-derived neurotrophic factor as a biomarker with left ventricular echocardiographic indices for potential diagnosis of coronary artery disease

Abstract: Brain-derived neurotrophic factor (BDNF) plays a central pivotal role in the development of the cardiovascular system. Recent evidence suggests that BDNF has adverse subclinical cardiac remodeling in participants with cardiovascular disease risk factors. Relating serum BDNF levels with two-dimensional echocardiographic indices will provide insights into the BDNF mediated pathophysiology in coronary artery disease (CAD) that may shed light upon potential diagnostic biomarkers. For the study, 221 participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…In the article by K.G. Monisha et al, it was also shown that the level of BDNF was significantly lower in individuals with CAD (30.69 ± 5.45 ng/mL) than in the control group (46.58 ± 7.95 ng/mL) [23]. It was confirmed that the expression of BDNF receptor was significantly reduced in patients with coronary atherosclerosis [12].…”
Section: Innervation Of Fat Cells Lipolysis Regulationmentioning
confidence: 83%
See 3 more Smart Citations
“…In the article by K.G. Monisha et al, it was also shown that the level of BDNF was significantly lower in individuals with CAD (30.69 ± 5.45 ng/mL) than in the control group (46.58 ± 7.95 ng/mL) [23]. It was confirmed that the expression of BDNF receptor was significantly reduced in patients with coronary atherosclerosis [12].…”
Section: Innervation Of Fat Cells Lipolysis Regulationmentioning
confidence: 83%
“…This is due to their participation in the control of the functioning of the nervous, immune, endocrine, and vascular systems, as well as in initiation and resolution of inflammation. Currently, there are data on the role of NTF in the pathogenesis of metabolic [14] and neurodegenerative diseases [15][16][17][18][19], along with cardiovascular pathology [20][21][22][23][24][25]. In recent years, the attention of scientists has been attracted by the brainderived neurotrophic factor (BDNF), which is a member of one of the NTF families.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Brain-derived neurotrophic factor (BDNF) regulates neurotrophin and neuronal survival in the brain, exerting important functions in the survival, growth, differentiation, and repair of cells, synaptic plasticity, and adult/embryonic neurogenesis in the neurons of the central nervous system by stimulating tropomyosin receptor kinase B [ 19 , 20 ]. BDNF is a pivotal player in the progression of the cardiovascular system and a low circulating BDNF level is linked with higher cardiovascular risks [ 21 , 22 ]. Moreover, the level of serum BDNF is reduced in HF patients [ 23 ], indicating the correlation between BDNF and CHF.…”
Section: Introductionmentioning
confidence: 99%